Účinek redistribučního mechanismu na vývoj regionálních disparit v ČR - Zdražil Pavel (Gaudeamus, 2015)
The issue of disparities and looking for its solutions belong among the most sensitive socio-economics topics which can be labelled as perpetual problem. These disparities are driven not only by economic differences within society but by differences among regions as well. One of the governments tool to fight against disparities is redistribution of wealth via public finance. The main aim of this paper is to examine the influence of redistribution mechanism on development of disparities - in the regional aspect - within the Czech Republic. Based on empirical results, we can suggest that the mechanism is inefficient in general, and therefore it doesn’t fulfil its macroeconomic function well.
Effect of redistribution mechanism on thedevelopment of regional disparities in the Czech Republic
Keywords: disparity; redistribuční mechanismus; dotace; kraje ČR; disparities; redistribution mechanism; subsidies; regions of the Czech Republic